2021
DOI: 10.7547/19-151
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Tibiotalocalcaneal Arthrodesis with a Femoral Nail

Abstract: Background Retrograde intramedullary nailing for tibiotalocalcaneal arthrodesis (TTCA) is used for severe hindfoot deformities, end-stage arthritis, and limb salvage. The procedure is technically demanding, with complications such as infection, hardware failure, nonunion, osteomyelitis, and possible limb loss or death. This study reports the outcomes and complications of patients undergoing TTCA with a femoral nail, which is widely available and offers an extensive range of lengths and diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…We preferred using a femoral nail because femoral nails provide a comprehensive size range in terms of length and diameter and have less inherent angulation. Moreover, the use of femoral nails for TTCA has been well documented in the literature with excellent results [7][8][9][10]. In a prospective study [9], TTCA was performed using a retrograde femoral nail among 29 patients and showed that the mean American Orthopaedic Foot and Ankle Society Ankle-Hindfoot Score increased from 46 to 71 after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We preferred using a femoral nail because femoral nails provide a comprehensive size range in terms of length and diameter and have less inherent angulation. Moreover, the use of femoral nails for TTCA has been well documented in the literature with excellent results [7][8][9][10]. In a prospective study [9], TTCA was performed using a retrograde femoral nail among 29 patients and showed that the mean American Orthopaedic Foot and Ankle Society Ankle-Hindfoot Score increased from 46 to 71 after surgery.…”
Section: Discussionmentioning
confidence: 99%